PENGARUH PERBEDAAN RENTANG WAKTU PERENDAMAN LARVA DALAM LARUTAN PROBITIK TERHADAP KELULUSHIDUPAN DAN PERTUMBUHAN IKAN SELAIS (Kryptopterus lais) - Haprizal Efendi; Agusnimar Agusnimar; Edi Warman (DINAMIKA PERTANIAN, 2016)
This research was conducted in order to determine the effect of interval time of submersion of larvae in solution of probiotics on the survival and growth of Kryptopterus lais. The experiment design used was completely randomized design, consisted four treatments and three replications i.e. without submersion of larvae in probiotic’s solution (P1); submersion of larvae in probiotic’s solution with interval one times in 2 days (P2); submersion of larvae in probiotic’s solution with interval one times in 4 days; submersion of larvae in probiotic’s solution with interval one times in 6 days (P3). The results showed that the treatment of P3 provided the best survival rate (91.33%), absolute body weight (0.60g) and absolute body length (5.6 cm). The interval time of submersion of fish larvae in probiotic’s solution had not significant difference on survival rate and growth rate of K.lais larvae (P>0,05).